2013
DOI: 10.7785/tcrt.2012.500347
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Automatic Contour Propagation for 4D Treatment Planning Using Multiple Metrics

Abstract: The aim of this work is to provide insights into multiple metrics clinical validation of deformable image registration and contour propagation methods in 4D lung radiotherapy planning. The following indices were analyzed and compared: Volume Difference (VD), Dice Similarity Coefficient (DSC), Positive Predictive Value (PPV) and Surface Distances (SD). The analysis was performed on three patient datasets, using as reference a ground-truth volume generated by means of Simultaneous Truth And Performance Level Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
(78 reference statements)
2
18
0
Order By: Relevance
“…28 , 29 The cord, heart, and lung tumor DSC values using segmentation or propagation have also been reported to range between 0.8 and 0.9 for clinically acceptable results. 23 , 24 Values for the quantitative accuracy metrics in Figure 4 of the present study were in agreement with these previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…28 , 29 The cord, heart, and lung tumor DSC values using segmentation or propagation have also been reported to range between 0.8 and 0.9 for clinically acceptable results. 23 , 24 Values for the quantitative accuracy metrics in Figure 4 of the present study were in agreement with these previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
“…In an interobserver contouring investigation, DSC for thoracic structures was reported to range between 0.74 for esophagus and 0.96 for lungs, with the esophagus generating the largest interobserver variability 13 . Other studies report esophagus DSC ranging from 0.7 to 0.8 and HD of approximately 10 mm 23, 24, 25. Studies reporting lung contour propagation accuracy have found MDA, HD, and DSC values ranging from 1.5 to 2 mm, 20 to 25 mm, and 0.91 to 0.96, respectively 4, 23, 24, 26, 27.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the intra‐ and inter‐observer variation is common, leading to multiple ground truths. To minimize the uncertainty in the scientific ground truth, the simultaneous truth and performance level estimation ( STAPLE) algorithm was developed40 and applied to evaluate tumor delineation in radiotherapy planning of lung, liver, and pancreatic cancer using CT or 4DCT 41, 42, 43, 44. Based on the statistics of a group of clinical ground truths from multiple physicians, the most probable ground truth can be computed and used as the scientific ground truth.…”
Section: Introductionmentioning
confidence: 99%